Project development of open education platform for the company competitiveness - Pichugina, Maryna; Artemenko, Lina (Serbian Journal of Management, 2022)
Since the corporate e-learning platforms is a relatively new, unexplored frontier, this paper is intended to provide a case and to offer a framework for project development. The aim of this study is to discover the development of open education platform for maintain the company competitiveness.  This paper describes the idea and the stages of the project to create a corporate online learning platform. The general background for education platform project in Ukraine is presented; the reasons for choosing the Igor Sikorsky KPI as software and content developers are revealed. Also, it is highlighted that just on-line resources do not lead to realizing the potential of platforms; it requires technologies that make platform interactive and engaging. Methodology: The case study in this article introduces an initiative to create online platform for a Ukraine-based company. Comparative research methods are used for analysis of Ukraine's position on the level of ICT development by international indices, with vertical comparison extensively for determination the level of ICT development in comparison with other countries. Benchmarking method is realized for actualization the corporate e-learning in Ukraine. The traditional method of dividing the project into stages, which involves determining the actions to be completed, is used.Findings: The results showed positive values in the different dimensions analyzed: (I) Potential of learning platform in corporate development, (II) The design of e-learning platform, (III) The project steps in the open education platform creation and (IV) The professional practice of «company-university» cooperation. Implications: Our implication in the problems of company development horizons, which are determined by modern challenges and opportunities of digitalization. Оnline platforms launched by «company-university» teams can provide thematic, social and digital enrichment for all agents involved. Originality: The main contribution is revealing the project of open education platform to maintain the Ukrainian company competitiveness with integration the Ukrainian university experience. The case has no analogies in Ukraine.
Keywords: education platforms; project development; e-learning; company-university collaboration; company competitiveness